Editorial: do thiopurines and biologics decrease the risk of colectomy? Authors' reply. Issue 9 (11th October 2017) - Eriksson, C.; Cao, Y.; Rundquist, S.; Zhulina, Y.; Henriksson, I.; Montgomery, S.; Halfvarson, J.
Abstract : This paper is linked to Allin and Jess, and Eriksson et al papers. To view these articles visithttps://doi.org/10.1111/apt.14292 andhttps://doi.org/10.1111/apt.14268 .